Materials for sustainable sites : a complete guide to the evaluation, selection, and use of sustainable construction materials - Calkins, Meg (Hoboken, N.J. : Wiley, 2009)
This title provides current information on construction materials for sustainable sites. Part one introduces tools, techniques, ideologies and resources for evaluating, sourcing and specifying sustainable site materials. Part two devotes a chapter each to 16 types of materials - both conventional and emerging green materials.
Materials for sustainable sites defined -- Background : inputs, outputs and impacts of construction materials -- Evaluating the environmental and human health impacts of materials -- Resource reuse : designing with and specifying reclaimed, reprocessed and recycled-content materials -- Concrete -- Earthen materials -- Brick masonry -- Asphalt pavement -- Aggregates and stone -- Wood and wood products -- Metals -- Plastics and rubber -- Biobased materials / by Ruth Stafford -- Appendix A: Embodied energy and embodied carbon of construction materials by weight -- Appendix B: Health and environmental impacts of hazardous air pollutants and metals related to construction materials.
Includes bibliographical references and index.
boek